Evaluation of the LabChecking Platform Using Webqual 4.0 with the Importance Performance Analysis Method - Imaroh, Tukhas Shilul; Ginting, Putri Irene Agina (ARE Publisher, 2024)
Objectives: The objective of this research is to analyze, measure and improve the quality of website services based on the WebQual 4.0 method with the dimensions of Usability, Information Quality, and Service Interaction Quality as well as the Importance Performance Analysis (IPA) method. Methodology: This research is using the quantitative descriptive method. Quantitative descriptive method, usually this method will be used as the main research in describing a word or number that has a certain meaning. In this study, the following stages were carried out: Finding: Since the pandemic, one of the innovations of technological development is the medical services platform that helps access in the health sector where there are no distance limitations between patients and doctors. In Indonesia, there have been various health service platforms that support access to health care facilities, launched by various parties from these startup companies. One of the startups that is the choice of the community today is a medical services platform such as Labchecking. Conclusion: The final results that have been measured have an average value of the level of perception (performance) and expectations (importance) of 2.85 and 3.54. For the average results obtained based on the suitability level value of 80.73% with the largest suitability level value found in the service interaction quality dimension, which is 81.72%, while for the results of the average value of the gap (GAP) of -0.681 with the largest gap value found in the usability dimension, which is -0.700.